THE ONTOLOGICAL FEATURES OF VERB PHRASES IN NATIONAL GEOGRAPHIC’S VISIONS OF MARS - Wedhowerti Wedhowerti (Universitas Islam Sumatera Utara (UISU), 2021)
Verb Phrase (VP) is one of the most important types of phrase for its function. It provides information about the subject of the sentence. Verb Phrase itself has more than one type. It also has ontological aspect, an aspect by which a certain situation is represented. This aspect is made up by features. This study aims at finding out and analyzing the types of VP and their ontological features in National Geographic’s Visions of Mars. By analyzing and understanding the types of VP and their ontological features, readers understand the discourse more. They gain more perspective syntactically. This study employs syntactic approach and is qualitative in nature. The results yield three different types of VP, i.e. action, process, and state where action VP places the highest position. There are four ontological features found in Visions of Mars, i.e. dynamic, agentive, non-evolving, and evolving. The findings imply how Visions of Mars is structured. The deeds are mostly conducted or done by an agent and show prompt situations.